Philosophy of History and Action
254 p.
Keywords: This volume contains the proceedings of the First Jerusalem Philosophical Encounter - started by the Hebrew University Institute of Philosophy (now the S. H. Bergman Centre for Philosophical Studies), which took place on December 28-31, 1974. In recent years the culture-gap that separates philosophers seems slowly - indeed much too slowly - to be narrowing. Although short circuits in communication still do happen and mutual disrespect has not vanished, it is becoming unfashionable to demonstrate ignorance of another philosophical tradition or to shrug it off with a supercilious smile. Perhaps dialectically, the insufficiency of any self-centred view that tries to immunize itself to challenges from without starts to disturb it from within. Moreover, as the culture- (and language-) bound nature of many philosophical divergencies is sinking more deeply into consciousness, the irony of an attitude of intolerance to them becomes more apparent. Our aim was to make a modest contribution to this development. We did not, however, mean to confuse genuine differences and problems in communication. Consequently, the more realistic term "encounter" was preferred to the idealizing "dialogue. " The Israeli hosts, themselves trained in a variety of philosophical traditions, felt that there is something in between real dialogue on the one hand and mutual estrangement on the other, and wished to provide a meeting place for it.